Peripheral B Lymphocyte Serves as a Reservoir for the Persistently Covert Infection of Mandarin Fish Siniperca chuatsi Ranavirus - Wenfeng Zhang; Hui Gong; Qianqian Sun; Yuting Fu; Xiaosi Wu; Hengwei Deng; Shaoping Weng; Jianguo He; Chuanfu Dong (Viruses)
Mandarin fish ranavirus (MRV) is a distinctive member among the genus Ranavirus of the family Iridoviridae. The persistently covert infection of MRV was previously observed in a natural outbreak of MRV, but the underlying mechanism remains unclear. Here, we show that mandarin fish peripheral B lymphocytes are implemented as viral reservoirs to maintain the persistent infection. When mandarin fish were infected with a sublethal dosage of MRV under a nonpermissive temperature (19 °C) and a permissive temperature (26 °C), all of the fish in the 19 °C group survived and entered the persistent phase of infection, characterized by a very low viral load in white blood cells, whereas some of the fish died of MRV infection in the 26 °C group, and the survival fish then initiated a persistent infection status. Raising the temperature, vaccination and dexamethasone treatment can reactivate the quiescent MRV to replicate and result in partial mortality. The viral reservoir investigation showed that IgM+-labeled B lymphocytes, but not CD3Δ+-labeled T lymphocytes and MRC-1+-labeled macrophages, are target cells for the persistent infection of MRV. Moreover, the reactivation of the quiescent MRV was confirmed through a non-TLR5 signal pathway manner. Collectively, we demonstrate the presence of the B cell-dependent persistent infection of ranavirus, and provide a new clue for better understanding the complex infection mechanism of vertebrate iridovirus.